The Relationship of Plasma Homocysteine Levels and the Methylenetetrahydrofolate Reductase C677T Gene Polymorphism to Ankylosing Spondylitis in a Chinese Population - Ni MAO; Jinwei CHEN; Wenfeng PENG; Lixiao CHEN; Xi XIE (Archives of Rheumatology, 2012)
Objectives: The aim of this study was to investigate the relationship of both the plasma homocysteine (Hcy) level and N5,N10-methylenetetrahydrofolate reductase (MTFHR) gene polymorphism with ankylosing spondylitis (AS). Patients and methods: Two hundred Chinese patients with AS and 120 healthy controls were included. The plasma Hcy level was examined by enzyme-linked immunosorbent assay (ELISA), while the MTHFR gene polymorphism was analyzed by the polymerase chain reaction (PCR) and restriction fragment length polymorphism (RFLP). Results: The two groups were examined according to age, and no statistically significant differences were found. The plasma Hcy level in the AS group was significantly higher than the control group (t=24.402, p=0.000). The ratio of the T/T genotype mutation was different in the AS group and the control group (X2=9.874, p=0.002) There was no marked difference in the frequencies of the MTHFR C/C, or C/T genotype between the two groups. The plasma Hcy level of the T/T genotype was significantly higher than that of the C/T or C/C genotype in the AS group (q=6.496, p<0.01; q=12.088, p<0.01). Conclusion: Our study result showed that the plasma Hcy levels were significantly increased in patients with AS, and the MTHFR T/T genotype mutation was an important influential mechanism which precipitated hyperhomocysteinemia and might be related to AS.